Digitalize agriculture in Vietnam, opportunities and challenges - Khanh, Nguyen Quoc; Vang, Dang Quang (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2020)
Digitalization can transform the fundamentals of production and supply chain. Digitalization technology will shape both the future the benefits of manufacturing industries. In agriculture, this is even more important in the face of growing demand. For the past 30 years, Vietnam’s agriculture has remained with the traditional model, with a proven tendency to slow down and decrease quantity and quality of production. How to develop a completely modernize agriculture model to produce quality goods with high efficiency and competitiveness? What is the technological solution to advance each region’s agricultural development in the context of this Fourth technological revolution? In what ways will the economic regions have to adapt their mindsets, ways of thinking, and ways of action? The paper is based on a summary of studies to generalize the problems, assess the current situation, analyze the current applications of high technology and point out the opportunities and challenges that need to be addressed for Vietnamese agriculture.